Levels of acid sphingomyelinase (ASM) in Caenorhabditis elegans in microgravity - Gravely, Annabel; Vlasov, Alice; Freeman, Amy; Wu, Kay; Szewczyk, Nathaniel J.; D'Cruz, Robert; Batt, Jane (American Society for Gravitational and Space Research, 2018)
Both Amyotrophic Lateral Sclerosis (ALS) patients and astronauts in spaceflight suffer from muscle atrophy. Previous research suggests that the enzyme acid sphingomyelinase (ASM) may be involved in the pathogenesis of ALS, but it is not known if ASM influences muscle atrophy in microgravity. In this study, C. elegans were exposed to microgravity conditions on the International Space Station (ISS) within the confines of a Fluid Mixing Enclosure (FME). Return of the FME yielded 72,050 live nematodes, the first demonstration of C. elegans survival of space travel in an FME. After the nematodes returned to Earth, in much larger numbers than seen in previous FME experiments, the size and ASM expression levels in experimental worms were compared to control Earth-bound worms. C. elegans that returned from the ISS were larger in both length and cross-sectional area than the control worms, and they exhibited decreased expression of ASM-1 and ASM-2 proteins. Further research must be conducted to elucidate the role of ASM in muscle atrophy, as there were many limitations to this study. Understanding the role of ASM in muscle atrophy may lead to the discovery of novel targets for treatment of both ALS and muscle atrophy in microgravity. This study was a student led initiative and undertaken as a project within the Student Spaceflight Experiment Program (SSEP), under the auspices of the National Center for Earth and Space Science Education and the Arthur C Clarke Institute for Space Education.